The Influence of Quality Of Work Life and Employees’ Engagement to Organizational Commitment at Anita PhoneshopBaturaja - Mardiansyah, Muhamad; Rusdiah, Rusdiah; Rabiulkhri, Mailani (BIMA Journal (Business, Management, & Accounting Journal), 2022)
This study aims to analyze the effect of Quality of Work Life and Employee Engagement on Organizational Commitment. With employees at Anita Phoneshop Baturaja which is used as a case study. Primary and secondary data were used in this study. Secondary data were obtained from various sources such as journals, books and other related publications. Primary data was obtained by using a questionnaire distributed to respondents who were targeted. By using the slovin technique, the total sample obtained was 53 respondents. Multiple linear regression analysis method with SPSS 26 program was used to analyze the data. The results showed that Quality of Work Life and Employee Engagement had a positive and significant impact on Organizational Commitment, contributing 70.1% with the variable Quality of Work Life having a more dominant influence. This shows that the company should focus on maintaining and improving the organizational work climate technically and humanely in order to lead to a better quality of work life.